The The IoT Based Health Monitoring with Alcohol Detection And Control System (International Journal of Engineering and Computer Science, 2023)
Accidents caused due to drunken drive are increasing tremendously in this modern world. To prevent these kinds of accidents, we propose an IoT based health monitoring system with alcohol detection and control. The proposed project is designed to reduce accidents caused due to drunken driving. Globally the cases of accidents are increasing due to this aspect. In order to prevent these accident cases, in this project   an IoT based method has been designed. In that Arduino, Alcohol Sensor, Heart beat rate sensor, Global System for Mobile communication, Wi-Fi modem, are utilized. Once the alcohol rate and heart beat rate are exceeding the specified limit, the command will be given to the ignition system of the vehicle to stop the operation of the vehicle.